Design and Implementation Strategy of A Real-Time Personnel & Asset Tracking System for Underground Mine at PT. FREEPORT INDONESIA - Setiawan, Jati; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2012)
PT Freeport Indonesia (PTFI), an affiliate of Freeport-McMoRan Copper & Gold Inc., is a world class mining company that produces copper, gold, and silver concentrates using open-pit and underground mining methods. The accounting of all personnel who is working or temporary visiting underground mine at any times is not only required under mining regulation of the Government of Indonesia, but also part of the company’s core values in ensuring the safety and health of the employees. The hardware of existing Universal ID and tag-in/tag-out systems are not reliable for providing such a tracking system due to the aggressive underground environment, and are unable to detect the real-time location of every worker inside the underground mine in a case of a massive evacuation. With the new advancements in the real-time location system (RTLS) for mining industry, the use of Radio Frequency Identification (RFID) on top of Wireless-Fidelity (Wi-Fi) infrastructure as the chosen platform for a real-time personnel and asset tracking system in the underground mine environment has been made possible, supported by proven vendors, and aligned with global wireless technology standard for Freeport-McMoRan organization. The Freeport-McMoRan project management process workflow is used as the methodology for proposing the implementation plan. In order to prove the concept, gaining trust from the project stakeholders, and minimizing the overall project risk, a phased implementation approach should be used as it is considered the best deployment strategy for such high capital project. Keywords: Tracking System, Selection Criteria, Decision Making, Project Management, Underground Mine